Preparation method of super-hydrophobic / super-oleophylic nano TiO2 cotton cloth for oil-water separation

By activate the cotton cloth and coated TiO2 coating, the nano-broken structure is constructed, which solves the problems of poor durability and low separation efficiency of existing membrane separation materials, and achieves efficient oil-water separation and multiple reuse of materials.

CN119194840AInactive Publication Date: 2024-12-27XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411296094.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor durability and low separation efficiency of the surface functional layer of existing membrane separation materials lead to low oil-water separation efficiency during oil production and transportation.

Method used

The preparation method of superhydrophobic/super oleophilic nano-TiO2@ cotton cloth is adopted to construct a nano-coarse structure by activating the cotton cloth, TiO2 sol impregnation, air plasma treatment and hydrothermal reaction, and to enhance the superhydrophobic characteristics of the cotton cloth, and to improve the superhydrophobic characteristics of the cotton cloth. The surface is coated with TiO2 coating with ultra-wetting properties to form an efficient oil-water separation material.

Benefits of technology

The durability of the surface functional layer of the cotton cloth and the oil-water separation efficiency are improved, efficient oil-water separation is achieved, and the material is reused and regenerated through ultraviolet light irradiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194840A_ABST
    Figure CN119194840A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of super-hydrophobic / super-oleophylic nano TiO2 cotton cloth capable of being used for oil-water separation, and belongs to the technical field of oil-water separation, and the preparation method is specifically implemented according to the following steps: step 1, activating the cotton cloth; step 2, putting the activated cotton cloth into TiO2 sol for dipping treatment, and then performing centrifugal spin-drying and drying to obtain TiO2 gel coated cotton cloth; step 3, carrying out air plasma or oxygen plasma treatment on the TiO2 gel coated cotton cloth, and cooling to room temperature to obtain the super-hydrophilic TiO2 coated cotton cloth; and step 4, adding a low surface energy modifier into the TiO2 Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, and immersing the super-hydrophilic TiO2 (at) cotton cloth into the hydrothermal reaction solution for hydrothermal reaction to obtain the super-hydrophobic / super-oleophylic TiO2 Nps / TiO2 (at) cotton cloth. The cotton cloth surface functional layer prepared by the method is good in durability and high in separation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil-water separation, and in particular relates to a method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth which can be used for oil-water separation. Background Art

[0002] With the rapid development of modern industry, the demand for oil is increasing. Oil spills and oil pollution accidents caused by oil production and transportation are frequent. It is crucial to study a method for efficiently treating oily wastewater for both human society and the ecological environment. The commonly used method for treating oily wastewater is filtration separation. The filtration separation method achieves the separation of oil and water in the mixed liquid through selective permeation, with high separation efficiency and energy-saving and environmental protection in the separation process. Among them, the most frequently used is membrane separation, which mainly utilizes the wettability of the film. Common membrane separation raw materials include super-wetting metal mesh materials and porous inorganic ceramic membrane materials. Metal mesh has the advantages of high mechanical strength, excellent performance and wide application range, but the surface functional layer of the metal mesh has poor durability and is easy to break and fall off. Inorganic ceramic membranes have excellent mechanical strength and physical and chemical properties, but their pores are not easy to adjust, resulting in low separation efficiency and limited application range in industry. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation, so as to solve the problems of poor durability of the surface functional layer and low separation efficiency of existing membrane separation materials.

[0004] The technical solution adopted by the present invention is a method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation, which is specifically implemented according to the following steps:

[0005] Step 1, activating the cotton cloth;

[0006] Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth;

[0007] Step 3, subjecting the TiO2 gel@cotton cloth to air plasma or oxygen plasma treatment, and cooling to room temperature to obtain super-hydrophilic TiO2@cotton cloth;

[0008] Step 4, adding a low surface energy modifier to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for hydrothermal reaction, and obtaining a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth.

[0009] The present invention is also characterized in that:

[0010] The specific process of step 1 is: ultrasonically clean the cotton cloth in anhydrous ethanol, then soak the cleaned cotton cloth in a sodium carbonate solution, take it out, rinse it with deionized water and dry it, and activate the dried cotton cloth with air plasma or oxygen plasma.

[0011] The time of air plasma or oxygen plasma activation treatment is 30s to 180s, the working power is 90W to 180W, and the working current is 6A.

[0012] The specific process of step 2 is:

[0013] Step 2.1, tetrabutyl titanate and acetylacetone are mixed evenly, and ethanol is added to the mixed solution, magnetically stirred, and allowed to stand for aging to obtain a TiO2 sol;

[0014] Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol, taking it out and centrifuging it to dry it, and placing the dried cotton cloth in an oven to dry it to obtain TiO2 gel@cotton cloth.

[0015] In step 2.1, the molar ratio of tetrabutyl titanate to acetylacetone is 0.25 to 4:1; the concentration of TiO2 sol is 0.1 mol / L to 1.0 mol / L;

[0016] In step 2.2, the immersion time is 2 min to 10 min, the drying temperature is 50° C. to 100° C., and the drying time is 10 min to 35 min.

[0017] In step 3, the air plasma or oxygen plasma treatment time is 160s to 300s, the working power is 70W to 200W, and the working current is 6A.

[0018] The specific process of step 4 is:

[0019] Step 4.1, after tetrabutyl titanate, HNO3 and ethanol are uniformly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution;

[0020] Step 4.2, place the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introduce the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth. After sealing, put it in a drying oven for insulation, cool it to room temperature with the furnace, take it out and rinse it with deionized water, and then place it in an oven to dry to obtain super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth.

[0021] In step 4.1, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 30-40:0.8-1.2:0.75-1.15;

[0022] The concentration of the low surface energy modification solution is 20 g / L to 50 g / L, the low surface energy modifier in the low surface energy modification solution is any one or more of octadecyltrimethyloxysilane, dodecyltrimethoxysilane, hexadecyltrimethyloxysilane, and n-butyltrimethoxysilane, and the solvent is ethanol;

[0023] In step 4.2, the temperature of the drying oven is 140°C to 160°C, the insulation time is not less than 2 hours, the drying temperature is 80°C to 100°C, and the drying time is not less than 8 hours.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention provides a method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation. The method constructs a nano-rough structure on the surface of the cotton cloth by low surface energy modification and hydrothermal synthesis technology, further improving the super-hydrophobic property of the cotton cloth, and obtaining a super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that has the function of filtering and separating the oil phase component from the oil-water mixture. The surface functional layer of the cotton cloth has good durability and high oil-water separation efficiency.

[0026] (2) The present invention provides a method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation, wherein a TiO2 coating having super-wetting properties is coated on the cotton cloth, thereby giving the cotton cloth a high degree of oil-water selectivity;

[0027] (3) The preparation method of the super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth for oil-water separation of the present invention adopts cotton cloth as the base material, which has a high porosity and an easily adjustable pore size. In practical application, the pore size can be adjusted according to different oil-water separation systems;

[0028] (4) The super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth prepared by the method of the present invention utilizes the property of TiO2 photocatalytic degradation of the filter membrane surface to adsorb oil pollution to achieve the regeneration cycle and multiple reuse of the super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth oil-water filtration separation material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the XRD pattern of super hydrophobic / super oleophilic TiO2Nps / TiO2@cotton fabric prepared by the method of the present invention;

[0030] Figure 2 It is a diagram of the apparatus for conducting an oil-water separation experiment using super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton fabric prepared by the method of the present invention;

[0031] Figure 3 is a SEM image of super hydrophobic / super oleophilic TiO2Nps / TiO2@cotton fabric prepared by the method of the present invention;

[0032] Figure 4 FT-IR image of super hydrophobic / super oleophilic TiO2Nps / TiO2@cotton fabric prepared by the method of the present invention;

[0033] Figure 5 The water contact angle and oil contact angle of the super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton fabric prepared by the method of the present invention are shown. DETAILED DESCRIPTION

[0034] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] The preparation method of the super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth for oil-water separation of the present invention is specifically implemented according to the following steps:

[0036] Step 1, activating the cotton cloth;

[0037] The specific process is as follows: the cotton cloth is ultrasonically cleaned in anhydrous ethanol, and then the cleaned cotton cloth is soaked in a sodium carbonate solution with a mass concentration of 1% for 3 hours, and then rinsed with deionized water and dried. The dried cotton cloth is activated by air plasma or oxygen plasma for 30s to 180s, with a working power of 90W to 180W and a working current of 6A, so as to generate more oxygen-containing active groups, which is conducive to the chemical bond between TiO2 and cotton cloth;

[0038] Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth;

[0039] The specific process is:

[0040] Step 2.1, tetrabutyl titanate (titanium source) and acetylacetone (chelating agent) are mixed evenly, and ethanol (solvent) is added to the mixed solution, magnetically stirred for 2 hours, and allowed to stand for 4 hours to obtain TiO2 sol;

[0041] Wherein, the molar ratio of tetrabutyl titanate to acetylacetone is 0.25 to 4:1; the concentration of TiO2 sol is 0.1 mol / L to 1.0 mol / L;

[0042] Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol for 2 minutes to 10 minutes, taking it out and centrifugally drying it, and placing the dried cotton cloth in an oven at a temperature of 50 to 90° C. for drying for 10 minutes to 35 minutes to obtain TiO2 gel @ cotton cloth;

[0043] Step 3, subjecting the TiO2 gel@cotton cloth to air plasma or oxygen plasma treatment for 160s to 300s, with a working power of 70W to 200W and a working current of 6A, so as to fully degrade the organic matter in the gel layer, transform the gel layer into a ceramic layer, and give the cotton cloth super-hydrophilic properties, and obtain super-hydrophilic TiO2@cotton cloth after cooling to room temperature;

[0044] Step 4, adding a low surface energy modifier to a TiO2Nps (TiO2 nanoparticles) hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for a hydrothermal reaction, and constructing a hydrophobic TiO2Nps on the surface of the mediating layer through a hydrothermal reaction combined with a molecular self-assembly technique to obtain a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth;

[0045] The specific process is:

[0046] Step 4.1, after tetrabutyl titanate (titanium source), HNO3 (hydrolysis aid), and ethanol (solvent) are evenly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution;

[0047] Wherein, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 30-40:0.8-1.2:0.75-1.15;

[0048] The concentration of the low surface energy modification solution is 20 g / L to 50 g / L, the low surface energy modifier in the low surface energy modification solution is any one or more of octadecyltrimethyloxysilane, dodecyltrimethoxysilane, hexadecyltrimethyloxysilane, and n-butyltrimethoxysilane, and the solvent is ethanol;

[0049] Step 4.2, placing the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introducing the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth, sealing it and placing it in an electric hot air drying oven at a temperature of 140°C to 160°C for insulation for not less than 2 hours, cooling it to room temperature with the furnace, taking it out and rinsing it with deionized water, and then placing it in an oven at a temperature of 80°C to 100°C for drying for not less than 8 hours to obtain a super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth;

[0050] Step 5, drying the super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth after multiple uses, and then irradiating it with ultraviolet light with a main wavelength of 254nm for 40min to 50min, and repeating step 4, the super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth will restore its oil-water separation properties.

[0051] The principle of the present invention is as follows: the hydroxyl and carboxyl groups contained in the cotton cloth itself determine that it does not have super wetting properties and cannot be used alone as an oil-water separation filter material; a TiO2 inorganic coating with super wetting properties is coated on the cotton cloth, which gives the cotton cloth a high degree of oil-water selectivity. After the material is coated, the performance is stable, the membrane-base bonding force is strong, and it has excellent anti-corrosion performance and durability; air plasma or oxygen plasma treatment is used to obtain super hydrophilic TiO2@cotton cloth; a low surface energy modifier is added to the hydrothermal reaction liquid, and a nano rough structure is constructed on its surface through hydrothermal synthesis technology to further enhance the super hydrophobic properties of the cotton cloth, thereby obtaining super hydrophobic / super oleophilic nano TiO2@cotton cloth with high separation efficiency; in addition, TiO2 has photocatalytic properties. After repeated use, long-term irradiation with ultraviolet light can restore the super hydrophobic / super oleophilic properties of the cotton cloth, which is conducive to repeated use.

[0052] Example 1

[0053] Step 1, activating the cotton cloth;

[0054] The specific process is as follows: the cotton cloth is ultrasonically cleaned in anhydrous ethanol, then the cleaned cotton cloth is soaked in a 1% sodium carbonate solution for 3 hours, then taken out and rinsed with deionized water and dried, and the dried cotton cloth is activated by air plasma for 30 seconds, with a working power of 90W and a working current of 6A;

[0055] Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth;

[0056] The specific process is:

[0057] Step 2.1, 2.72 g of tetrabutyl titanate and 0.2 g of acetylacetone were mixed evenly, and 30.68 g of ethanol was added to the mixed solution, magnetically stirred for 2 h, and allowed to stand for 12 h to obtain a TiO2 sol with a concentration of 0.1 mol / L;

[0058] Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol for 2 minutes, taking it out and centrifuging it to dry, and drying the dried cotton cloth in an oven at a temperature of 50°C for 10 minutes to obtain TiO2 gel@cotton cloth;

[0059] Step 3, the TiO2 gel@cotton cloth is treated with air plasma for 160s, the working power is 70W, the working current is 6A, and after cooling to room temperature, a super-hydrophilic TiO2@cotton cloth is obtained (note: it can be quickly wetted by water, and the contact angle is 0°);

[0060] Step 4, adding a low surface energy modifier to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for hydrothermal reaction to obtain a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth;

[0061] The specific process is:

[0062] Step 4.1, after tetrabutyl titanate, HNO3 and ethanol are uniformly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution;

[0063] Among them, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 30:0.8:0.75;

[0064] The concentration of the low surface energy modification solution is 20 g / L, the low surface energy modification agent in the low surface energy modification solution is octadecyltrimethyloxysilane, and the solvent is ethanol;

[0065] Step 4.2, placing the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introducing the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth, sealing it and placing it in a drying oven at a temperature of 140°C for insulation for not less than 2 hours, cooling it to room temperature with the furnace, taking it out and rinsing it with deionized water, and then placing it in an oven at a temperature of 80°C for not less than 8 hours to obtain super-hydrophobic / super-oleophilic octadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth;

[0066] Depend on Figure 1 It can be seen that in the XRD spectrum of the superhydrophobic / superoleophilic octadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth, TiO2Nps presents an anatase crystal phase, which indicates that the TiO2Nps coating is successfully coated on the surface of the cotton cloth;

[0067] Use Figure 2 The three-way T-shaped horizontal bidirectional oil-water separation device shown in the figure has hydrophobic / super oleophilic octadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth fixed on the left and super hydrophilic TiO2@cotton cloth on the right. Water phase-chlorobenzene oil-water is poured from the upper port, chlorobenzene is filtered out from the left oil filter port, and water phase is filtered out from the right water filter port, thereby achieving oil-water separation. The adsorption test experiment of the material is carried out to examine its cyclic stability.

[0068] The superhydrophobic / superoleophilic octadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth has a chlorobenzene separation flux of 25188.38 L / m in the water phase-chlorobenzene oil-water mixed system. 2 h. After 24 h of cycle experiment, the separation flux dropped to 22344.89 L / m2 ·h;

[0069] Step 5, drying the superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth after multiple uses, irradiating it with ultraviolet light with a main wavelength of 254nm for 40min, and repeating step 4, the chlorobenzene separation flux in the water phase-chlorobenzene oil-water mixed system can be restored to 25000L / m 2 ·h or more.

[0070] Example 2

[0071] Step 1, activating the cotton cloth;

[0072] The specific process is as follows: the cotton cloth is ultrasonically cleaned in anhydrous ethanol, then the cleaned cotton cloth is soaked in a 1% sodium carbonate solution for 3 hours, then taken out and rinsed with deionized water and dried, and the dried cotton cloth is activated by oxygen plasma for 90 seconds, with a working power of 120W and a working current of 6A;

[0073] Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth;

[0074] The specific process is:

[0075] Step 2.1, 4.98 g of tetrabutyl titanate and 0.6 g of acetylacetone were mixed evenly, and 27.55 g of ethanol was added to the mixed solution, magnetically stirred for 2 h, and allowed to stand for 12 h to obtain a TiO2 sol with a concentration of 0.3 mol / L;

[0076] Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol for 4 minutes, taking it out and centrifuging it to dry, and drying the dried cotton cloth in an oven at 60°C for 25 minutes to obtain TiO2 gel@cotton cloth;

[0077] Step 3, the TiO2 gel@cotton cloth is subjected to oxygen plasma treatment for 210 s, the working power is 110 W, the working current is 6 A, and after cooling to room temperature, a super-hydrophilic TiO2@cotton cloth is obtained (note: it can be quickly wetted by water, and the contact angle is 0°);

[0078] Step 4, adding a low surface energy modifier to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for hydrothermal reaction to obtain a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth;

[0079] The specific process is:

[0080] Step 4.1, after tetrabutyl titanate, HNO3 and ethanol are uniformly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution;

[0081] Among them, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 35:0.9:0.8;

[0082] The concentration of the low surface energy modification solution is 30 g / L, the low surface energy modification agent in the low surface energy modification solution is dodecyltrimethoxysilane, and the solvent is ethanol;

[0083] Step 4.2, placing the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introducing the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth, sealing it and placing it in a drying oven at a temperature of 145°C for 2.5 hours, cooling it to room temperature with the furnace, taking it out and rinsing it with deionized water, and then placing it in an oven at a temperature of 80°C for not less than 8 hours to obtain a super-hydrophobic / super-oleophilic dodecyltrimethoxysilane-TiO2Nps / TiO2@cotton cloth;

[0084] The separation flux of petroleum ether in the water-petroleum ether oil-water mixed system of the superhydrophobic / superoleophilic dodecyltrimethoxysilane-TiO2Nps / TiO2@cotton cloth is 27355.26 L / m 2 h. After 24 h of cycle experiment, the separation flux dropped to 25608.56 L / m 2 ·h;

[0085] Step 5, drying the superhydrophobic / superoleophilic dodecyltrimethoxysilane-TiO2Nps / TiO2@cotton cloth after multiple uses, irradiating it with ultraviolet light with a main wavelength of 254nm for 45min, and repeating step 4, the separation flux of petroleum ether in the water phase-petroleum ether oil-water mixed system can be restored to 27000L / m 2 ·h or more.

[0086] Depend on Figure 3 It can be seen that 1115cm -1 The characteristic peak at 609cm -1 The characteristic peaks correspond to the bending vibration absorption peak of the Ti-OH group and the antisymmetric stretching vibration peak of the Ti-O-Ti bond, indicating that chemical bonding is indeed produced between the TiO2 inorganic coating and the cotton cloth.

[0087] Example 3

[0088] Step 1, activating the cotton cloth;

[0089] The specific process is as follows: the cotton cloth is ultrasonically cleaned in anhydrous ethanol, then the cleaned cotton cloth is soaked in a 1% sodium carbonate solution for 3 hours, then taken out and rinsed with deionized water and dried, and the dried cotton cloth is activated by oxygen plasma for 115 seconds, with a working power of 150W and a working current of 6A;

[0090] Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth;

[0091] The specific process is:

[0092] Step 2.1, 9.52 g of tetrabutyl titanate and 1.4 g of acetylacetone were mixed evenly, and 20.33 g of ethanol was added to the mixed solution, magnetically stirred for 2 h, and allowed to stand for 12 h to obtain a TiO2 sol with a concentration of 0.7 mol / L;

[0093] Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol for 6 minutes, taking it out and centrifuging it to dry, and drying the dried cotton cloth in an oven at a temperature of 50°C for 25 minutes to obtain TiO2 gel@cotton cloth;

[0094] Step 3, the TiO2 gel@cotton cloth is treated with oxygen plasma for 260s, the working power is 160W, the working current is 6A, and after cooling to room temperature, a super-hydrophilic TiO2@cotton cloth is obtained (note: it can be quickly wetted by water, and the contact angle is 0°);

[0095] Step 4, adding a low surface energy modifier to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for hydrothermal reaction to obtain a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth;

[0096] The specific process is:

[0097] Step 4.1, after tetrabutyl titanate, HNO3 and ethanol are uniformly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution;

[0098] Among them, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 40:1.2:1.15;

[0099] The concentration of the low surface energy modification solution is 35 g / L, the low surface energy modification agent in the low surface energy modification solution is hexadecyltrimethyloxysilane, and the solvent is ethanol;

[0100] Step 4.2, placing the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introducing the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth, sealing it and placing it in a drying oven at a temperature of 160°C for 2 hours, cooling it to room temperature with the furnace, taking it out and rinsing it with deionized water, and then placing it in an oven at a temperature of 90°C for not less than 8 hours to obtain a super-hydrophobic / super-oleophilic hexadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth;

[0101] The superhydrophobic / superoleophilic hexadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth has a cyclohexane separation flux of 24589.33 L / m in the water phase-cyclohexane oil-water mixed system. 2 h. After 24 h of cycle experiment, the separation flux dropped to 22241.55 L / m 2 ·h;

[0102] Step 5, dry the super hydrophobic / super oleophilic hexadecyltrimethyloxysilane-TiO2Nps / TiO2@cotton cloth after multiple uses, and then irradiate it with ultraviolet light with a main wavelength of 254nm for 50min, and repeat step 4, then the cyclohexane separation flux in the water phase-cyclohexane oil-water mixed system can be restored to 24000L / m 2 ·h or more.

[0103] Depend on Figure 4 It can be seen that when water droplets in the air fall on the surface of cotton cloth, they will form a spherical shape. Regardless of whether it is in the air or underwater, once the modified cotton cloth comes into contact with the oil agent, it will immediately and completely absorb the oil droplets, showing very excellent superhydrophobic / superoleophilic properties and a high degree of oil-water selectivity.

[0104] Depend on Figure 5 It can be seen that the material surface absorbs the oil agent instantly, with a contact angle of 0°, and the cotton cloth exhibits excellent superhydrophobic properties in the air, with a contact angle of 165°.

[0105] Example 4

[0106] Step 1, activating the cotton cloth;

[0107] The specific process is as follows: the cotton cloth is ultrasonically cleaned in anhydrous ethanol, then the cleaned cotton cloth is soaked in a 1% sodium carbonate solution for 3 hours, then taken out and rinsed with deionized water and dried, and the dried cotton cloth is activated by air plasma for 180 seconds, with a working power of 180W and a working current of 6A;

[0108] Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth;

[0109] The specific process is:

[0110] Step 2.1, 13.6 g of tetrabutyl titanate and 2 g of acetylacetone were mixed evenly, and 17.66 g of ethanol was added to the mixed solution, magnetically stirred for 2 h, and allowed to stand for 12 h to obtain a TiO2 sol with a concentration of 1 mol / L;

[0111] Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol for 10 minutes, taking it out and centrifuging it to dry, and drying the dried cotton cloth in an oven at 90°C for 35 minutes to obtain TiO2 gel@cotton cloth;

[0112] Step 3, the TiO2 gel@cotton cloth was subjected to oxygen plasma treatment for 300s, with a working power of 200W and a working current of 6A, and after cooling to room temperature, a super-hydrophilic TiO2@cotton cloth was obtained (note: it can be quickly wetted by water, and the contact angle is 0°);

[0113] Step 4, adding a low surface energy modifier to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for hydrothermal reaction to obtain a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth;

[0114] The specific process is:

[0115] Step 4.1, after tetrabutyl titanate, HNO3 and ethanol are uniformly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution;

[0116] Among them, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 40:1.2:1.15;

[0117] The concentration of the low surface energy modification solution is 50 g / L, the low surface energy modification agent in the low surface energy modification solution is n-butyltrimethoxysilane, and the solvent is ethanol;

[0118] Step 4.2, placing the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introducing the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth, sealing it and placing it in a drying oven at a temperature of 160°C for 3 hours, cooling it to room temperature with the furnace, taking it out and rinsing it with deionized water, and then placing it in an oven at a temperature of 100°C for not less than 8 hours to obtain super-hydrophobic / super-oleophilic n-butyltrimethoxysilane-TiO2Nps / TiO2@cotton cloth;

[0119] The superhydrophobic / superoleophilic n-butyltrimethoxysilane-TiO2Nps / TiO2@cotton cloth has a gasoline separation flux of 23768.32 L / m in the NaCl phase-gasoline oil-water mixture system. 2h. After 24 h of cycle experiment, the separation flux dropped to 21845.96 L / m 2 ·h;

[0120] Step 5, the super hydrophobic / super oleophilic n-butyl trimethoxysilane-TiO2Nps / TiO2@cotton cloth was dried after multiple uses, and then irradiated with ultraviolet light with a main wavelength of 254nm for 40min, and step 4 was repeated. The gasoline separation flux in the NaCl phase-gasoline oil-water mixture system can be restored to 23000L / m 2 ·h or more.

[0121] The present invention adopts cotton cloth as the substrate, which is green and pollution-free in source and low in price. The cost of preparing the filter material by using cotton cloth as the substrate is lower.

Claims

1. A method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation, characterized in that: Follow the steps below to implement it: Step 1, activating the cotton cloth; Step 2, placing the activated cotton cloth into the TiO2 sol for immersion treatment, and then centrifugally drying and drying to obtain TiO2 gel @ cotton cloth; Step 3, subjecting the TiO2 gel@cotton cloth to air plasma or oxygen plasma treatment, and cooling to room temperature to obtain super-hydrophilic TiO2@cotton cloth; Step 4, adding a low surface energy modifier to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution, immersing the superhydrophilic TiO2@cotton cloth in the hydrothermal reaction solution for hydrothermal reaction, and obtaining a superhydrophobic / superoleophilic TiO2Nps / TiO2@cotton cloth.

2. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation according to claim 1, characterized in that: The specific process of step 1 is: ultrasonically clean the cotton cloth in anhydrous ethanol, then soak the cleaned cotton cloth in a sodium carbonate solution, take it out, rinse it with deionized water and dry it, and activate the dried cotton cloth with air plasma or oxygen plasma.

3. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation according to claim 2, characterized in that: The time of air plasma or oxygen plasma activation treatment is 30s to 180s, the working power is 90W to 180W, and the working current is 6A.

4. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation according to claim 1, characterized in that: The specific process of step 2 is: Step 2.1, tetrabutyl titanate and acetylacetone are mixed evenly, and ethanol is added to the mixed solution, magnetically stirred, and allowed to stand for aging to obtain a TiO2 sol; Step 2.2, immersing the cotton cloth treated in step 1 in the TiO2 sol, taking it out and centrifuging it to dry it, and placing the dried cotton cloth in an oven to dry it to obtain TiO2 gel@cotton cloth.

5. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation according to claim 4, characterized in that: In step 2.1, the molar ratio of tetrabutyl titanate to acetylacetone is 0.25 to 4:1; the concentration of TiO2 sol is 0.1 mol / L to 1.0 mol / L; In step 2.2, the immersion time is 2 min to 10 min, the drying temperature is 50° C. to 100° C., and the drying time is 10 min to 35 min.

6. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation according to claim 1, characterized in that: In step 3, the air plasma or oxygen plasma treatment time is 160s to 300s, the working power is 70W to 200W, and the working current is 6A.

7. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth for oil-water separation according to claim 1, characterized in that: The specific process of step 4 is: Step 4.1, after tetrabutyl titanate, HNO3 and ethanol are uniformly mixed to obtain a TiO2Nps hydrothermal precursor reaction solution, a low surface energy modification solution is added to the TiO2Nps hydrothermal precursor reaction solution to obtain a hydrothermal reaction solution; Step 4.2, place the super-hydrophilic TiO2@cotton in a hydrothermal reactor, and introduce the hydrothermal reaction liquid into the reactor to completely immerse the super-hydrophilic TiO2@cotton cloth. After sealing, put it in a drying oven for insulation, cool it to room temperature with the furnace, take it out and rinse it with deionized water, and then place it in an oven to dry to obtain super-hydrophobic / super-oleophilic TiO2Nps / TiO2@cotton cloth.

8. The method for preparing super-hydrophobic / super-oleophilic nano-TiO2@cotton cloth that can be used for oil-water separation according to claim 7, characterized in that: In step 4.1, the mass ratio of ethanol, tetrabutyl titanate and HNO3 is 30-40:0.8-1.2:0.75-1.15; The concentration of the low surface energy modification solution is 20 g / L to 50 g / L, the low surface energy modifier in the low surface energy modification solution is any one or more of octadecyltrimethyloxysilane, dodecyltrimethoxysilane, hexadecyltrimethyloxysilane, and n-butyltrimethoxysilane, and the solvent is ethanol; In step 4.2, the temperature of the drying oven is 140°C to 160°C, the insulation time is not less than 2 hours, the drying temperature is 80°C to 100°C, and the drying time is not less than 8 hours.